Lemuru Fish (Sardinella Lemuru) Oil effects on Body Weight of Wistar Rats Induced by Trans Fatty Acids - Abdurrahman Ali; Annis Catur Adi; Sri Adiningsih (poltekkes kemenkes mataram, 2022)
The content of EPA and DHA in lemuru fish oil can be used to prevent obesity risk factors. This study aims to determine the effect of purified lemuru fish oil on the weight of Wistar rats induced by trans fatty acids. This research is an experimental study using a randomized block design with a post test only control group. The research sample was 30 male Wistar rats aged two to three months, grouped into two control groups (K) which were given standard feed (K0) and those given standard feed after two weeks of trans fatty acid induction (K1) and three treatment groups (P). ) with lemuru fish oil intervention as much as 0.34 ml (P1), 0.67 ml (P2), and 1.34 ml (P3). The induction material was 2.3 g of liquid margarine, containing 3.8% trans fatty acids. The intervention material was lemuru fish oil from the purification process containing 18.05% EPA and 9.37% DHA. Induction of margarine for two weeks made the body weight of the rats increased by 27.90% (P2) compared to the control (K0) 16.06%. After the intervention period of lemuru fish oil for three weeks, the weight of the treatment group P1 (18.53%), P2 (14.74%), and P3 (13.19%) was lower than the control group K0 (22.79%) and K1 (25.31%).